Phylogenetic Characterization of Tomato chlorosis virus Population in Korea: Evidence of Reassortment between Isolates from Different Origins - Lee, Ye-Ji (Plant Pathol J, 2018)
Tomato chlorosis virus (ToCV) is a whitefly-transmitted and phloem-limited crinivirus. In 2013, severe interveinal chlorosis and bronzing on tomato leaves, known symptoms of ToCV infection, were observed in greenhouses in Korea. To identify ToCV infection in symptomatic tomato plants, RT-PCR with ToCV-specific primers was performed on leaf samples collected from 11 tomato cultivating areas where ToCV-like symptoms were observed in 2013 and 2014. About half of samples (45.18%) were confirmed as ToCV-infected, and the complete genome of 10 different isolates were characterized. This is the first report of ToCV occurring in Korea. The phylogenetic relationship and genetic variation among ToCV isolates from Korea and other countries were also analysed. When RNA1 and RNA2 are analysed separately, ToCV isolates were clustered into three groups in phylogenetic trees, and ToCV Korean isolates were confirmed to belong to two groups, which were geographically separated. These results suggested that Korean ToCV isolates originated from two independent origins. However, the RNA1 and RNA2 sequences of the Yeonggwang isolate were confirmed to belong to different groups, which indicated that ToCV RNA1 and RNA2 originated from two different origins and were reassorted in Yeonggwang, which is the intermediate point of two geographically separated groups.